1997
DOI: 10.1007/bf02318951
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of haploid plants from anther cultures of the Asiatic hybrid lily ‘Connecticut King’

Abstract: A system for producing haploid plants from anther cultures was developed for the Asiatic hybrid lily 'Connecticut King'. Anthers containing microspores at the mid-to late-uninucleate stages were cultured on MS media supplemented with various plant growth regulators. Microspores containing 3 or 4 vegetative-like nuclei were observed 2 to 3 weeks later, and yellowish nodular calluses appeared within dehisced anthers 2 to 3 months after culture. Picloi'am was superior to 2,4-D for inducing nodular calluses. Anthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
8

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 11 publications
2
22
0
8
Order By: Relevance
“…This result is consistent with the results obtained by Han et al (1997Han et al ( , 2000, whereby picloram was found to be essential for induction and maintenance of calli in cultured anthers of Lilium species. Those researchers showed that picloram was a favorable auxin for inducing yellowish nodular calli in anther cultures of the cultivar 'Connecticut King' (Han et al, 1997) and it also was suitable for maintaining haploid calli in this cultivar (Han et al, 2000). One of the principal conclusions of this study is that silver nitrate (at a concentration of 5 mg L -1 ) should be routinely used in the anther culture protocol of borage in order to delay callus browning and to increase the androgenic responses.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with the results obtained by Han et al (1997Han et al ( , 2000, whereby picloram was found to be essential for induction and maintenance of calli in cultured anthers of Lilium species. Those researchers showed that picloram was a favorable auxin for inducing yellowish nodular calli in anther cultures of the cultivar 'Connecticut King' (Han et al, 1997) and it also was suitable for maintaining haploid calli in this cultivar (Han et al, 2000). One of the principal conclusions of this study is that silver nitrate (at a concentration of 5 mg L -1 ) should be routinely used in the anther culture protocol of borage in order to delay callus browning and to increase the androgenic responses.…”
Section: Discussionsupporting
confidence: 93%
“…These were 10-15 mm in diameter, light yellow, nodular, and occasionally contained shoots and roots. The filament-derived calli efficiently produced shoots following their transfer to regeneration medium, which consisted of MS medium, 0.1 mg/l PIC, 0.01 mg/l BA, 30 g/l sucrose, and 3 g/l gellan gum (Han et al 1997).…”
Section: Plant Materialsmentioning
confidence: 99%
“…We hope that publication of this list will help in further application of DH technology in crop improvement and basic research. Shamina, 1986, 1993;Contolini and Menzel, 1987;Stelly et al, 1988;Bajaj and Gill, 1997;Khushwinder et al, 1998Guizotia abyssinica a Makhmudov, 1978Chaudhari, 1979;Mahill et al, 1984;Sarvesh et al, 1993;Adda et al, 1994 Mezzarobba and Jonard, 1986;Hongyuan et irr al., 1986;Gelebart and San, 1987;Gurel et al, 1991;Thengane et al, 1994;Coumans and Zhong, 1995;Zhong et al, 1995;Nurhidayah et al, 1996;Badigannavar and Kuruvinashetti, 1996;Todorova et al, 1997;Friedt et al, 1997;Saji and Sujatha, 1998;Todorova and Ivanov, 1999 Dryanovska, 1966;Prakash and Giles, 1986;Miki-Hirosige et al, 1988;Qu et al, 1988;Han et al, 1997Han et al, , 1999 Rose et al, 1987a;Pasakinskiene et al, 1997;Humphreys et al, 1998;Zare et al, 1999Rose et al, 1987a,b Ormerod and Caligari, 1994Sator et al, 1982Fan et al, 1982Gulshan et al, 1981Zagorska et al, ...…”
mentioning
confidence: 97%